Health trajectories of international humanitarian aid workers: growth mixture modelling findings from a prospective cohort study - Kaz de Jong; Saara. E. Martinmäki; Hans te Brake; Ivan Komproe; Rolf J. Kleber; Joris F. G. Haagen (BJPsych Open, 2023)
Background Most staff stay healthy during humanitarian work, although some worsen. Mean scores on health indicators may be masking individual participants struggling with health issues.